Ratiometric Detection of Viscosity Using a Two‐Photon Fluorescent Sensor. Issue 5 (19th December 2012) - Liu, Fei; Wu, Tong; Cao, Jianfang; Cui, Shuang; Yang, Zhigang; Qiang, Xinxin; Sun, Shiguo; Song, Fengling; Fan, Jiangli; Wang, Jingyun; Peng, Xiaojun
<x xml:space="preserve">Abstract</x> In the thick of it: A carbazole‐based cyanine derivative has been used as a ratiometric fluorescent sensor to detect mitochondrial viscosities over the range 1–950 cP within live cells and living tissues by using two‐photon microscopy. Its success is based on the fast‐ and low‐barrier rotation around its methine bond (see figure) and the huge increase of the fluorescence quantum yield (QY) from the loss of mobility in viscous media.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>